Effect of maternal baboon (Papio sp.) dietary mismatch in pregnancy and lactation on post‐natal offspring early life phenotype. Issue 4 (26th April 2019) - Li, Cun; Jenkins, Susan; Huber, Hillary F.; Nathanielsz, Peter W.
Abstract: Background: Non‐human primate models of developmental programing by maternal mismatch between pregnancy and lactation diets are needed for translation to human programing outcomes. We present baboon offspring morphometry from birth to 3 years, and blood cortisol and adrenocorticotropin (ACTH) from 2 to 24 months. Methods: Control mothers ate chow; mismatch mothers ate 30% less than controls during pregnancy and high‐fat high‐energy diet through lactation. Results: Mismatch mothers lost weight during pregnancy. At birth, there were trends toward lower weight in mismatch offspring of both sexes ( P  = 0.06). From 0‐3 years, catch‐up growth occurred. Mismatch offspring male and female body weight increased faster than controls ( P  < 0.001). Mismatch female offspring showed greater increase in BMI ( P  < 0.001) and abdominal circumference ( P  = 0.008) vs controls. ACTH and cortisol slopes from 2 to 24 months of age were similar between groups in both sexes. Cortisol and ACTH increased after weaning in all groups. Conclusions: Mismatch produces sexually dimorphic post‐natal growth phenotypes.